Brief Report: Highly Active Antiretroviral Therapy Mitigates Liver Disease in HIV Infection. (1st July 2016) - Price, Jennifer C.; Seaberg, Eric C.; Phair, John P.; Witt, Mallory D.; Koletar, Susan L.; Thio, Chloe L.
Abstract : Abstract: To determine the impact of highly active antiretroviral therapy (HAART) on liver disease, we analyzed changes in the aspartate aminotransferase to platelet ratio index (APRI) pre- and post-HAART initiation among 441 HIV-monoinfected and 53 HIV-viral hepatitis–coinfected men. Before HAART, APRI increased 17% and 34% among the HIV-monoinfected and coinfected men, respectively. With HAART initiation, APRI decreased significantly in men who achieved HIV RNA of <500 copies per milliliter: 16% for HIV-monoinfected and 22% for coinfected men. Decreases in APRI were dependent on HIV suppression. This protective effect of HAART decreased after 2 years, particularly in the HIV-monoinfected men. Abstract : Supplemental Digital Content is Available in the Text.